Our interaction was very productive: levels of reflection in learners' diaries in teletandem - Leone, Paola; Aranha, Solange [UNESP]; Spatti Cavalari, Suzi Marques [UNESP] (Adalsic, 2023)
This investigation aims to analyze what Brazilian participants say about teletandem interaction in their diaries and how (or if) they reflect upon it. Data are elicited from 350 diaries written in English and stored in MulTeC (Multimodal Teletandem Corpus) (Aranha & Lopes, 2019) and compiled by 333 fragments of text in which the most frequent word, interaction, (Leone et al., ongoing) occurs. The analytical framework is based on Moon ' s (2004) reflective writing and Garcia et al. (2017)'s proposal of metacognitive operations. Results reveal that 41% of the fragments featured mere descriptions of the events that occurred during the interaction, while most (59%) of them presented some degree of reflection. In our data, reflection seems to be based on: (i) the assessment of the interaction, in line with Garcia et al. (2017)' s proposal that assessment represents a frequent metacognitive operation; (ii) recognition of different elements that are relevant for language learning in teletandem, ie, partner's collaboration and task specificities. Our findings also indicate that the other metacognitive operations (setting goals, planning, selecting resources, managing emotions) support or motivate the judgments made by learners. This finding corroborates the notion proposed in other research (Moon, 2004, 2010) that writing diaries may promote reflection, which is a fundamental aspect of autonomous learning.
Keywords: learning diaries; telecollaboration; conscious reflection; teletandem